Performance of commercially-available cholesterol self-tests. (July 2021) - Kurstjens, Steef; Gemen, Eugenie; Walk, Selina; Njo, Tjin; Krabbe, Johannes; Gijzen, Karlijn; Elisen, Marc GLM; Kusters, Ron
Background: Hypercholesterolemia (plasma cholesterol concentration ≥5.2 mmol/L) is a risk factor for cardiovascular disease and stroke. Many different cholesterol self-tests are readily available at general stores, pharmacies and web shops. However, there is limited information on their analytical and diagnostic performance. Methods: We included 62 adult patients who required a lipid panel measurement (cholesterol, high-density lipoprotein (HDL), triglycerides and LDLcalc ) for routine care. The performance of five different cholesterol self-tests, three quantitative meters ( Roche Accutrend Plus, Mission 3-in-1 and Qucare ) and two semi-quantitative strip tests ( Veroval and Mylan MyTest ), was assessed according to the manufacturers' protocol. Results: The average plasma cholesterol concentration was 5.2 ± 1.2 mmol/L. The mean absolute relative difference (MARD) of the five cholesterol self-tests ranged from 6 ± 5% ( Accutrend Plus ) to 20 ± 12% ( Mylan Mytest ). The Accutrend Plus cholesterol meter showed the best diagnostic performance with a 92% sensitivity and 89% specificity. The Qucare and Mission 3-in-1 are able to measure HDL concentrations and can thus provide a cholesterol:HDL ratio. The Passing-Bablok regression analyses for the ratio showed poor performance in both self-tests ( Mission 3-in-1 : y = 1.62x–1.20; Qucare : y = 0.61x + 1.75). The Accutrend Plus is unable to measure the plasma high-density lipoprotein concentration. Conclusions/interpretation: The Accutrend Plus cholesterol meter (Roche) had excellent diagnostic and analytic performance. However, several of the commercially-available self-tests had considerably poor accuracy and diagnostic performance and therefore do not meet the required qualifications, potentially leading to erroneous results. Better regulation, standardization and harmonization of cholesterol self-tests is warranted.